Management and propagation of “cat´s claw” (Uncaria guianensis y U. tomentosa) by Tikuna indigenous communities of the southern Colombian Amazon - Garzón, Lina Paola Garzón; Calvo, Carlos Eduardo Franky (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Cat's claw (Uncaria guianensis (Aublet) J.F. Gmel and U. tomentosa (Willd. ex Roemer & Schultes) DC.) has been used in the traditional indigenous medicine. This plant stands out for its medicinal properties, which has generated a commercial interest. So far, there are many studies of U. tomentosa related with agroforestry management and propagation methods. However, the available information of Uncaria guianensis is limited, especially with its management in communities. With the aim to contribute with information about the management of these species and their propagation, It were conducted interviews, field trips with local guides and planting trials in Tikuna communities. It was found that the management of cat's claw species, mainly of the Uncaria guianensis, focuses both on the extraction and planting practices by stakes, as well as on the conservation of their natural regeneration. It was found that Uncaria tomentosa had a high mortality rate in the natural environment, since it was more susceptible to the adverse effects of environmental conditions. Otherwise, Uncaria guianensis had a greater survival especially in stubbles where stakes were treated with rooting hormones and it were planted and in soils enriched with organic fertilizer. The results of this research may contribute to the formulation of integrative management strategies, that allows a sustainable use of natural populations of cat's claw species in Amazonian communities.